Case Report: Combined umbilical cord blood and peripheral blood stem cell transplantation with donor lymphocyte infusion for R/R AML post CAR-CLL1 failure - Meng, Fanqiao; Liu, Yu; Zeng, Dongfeng (Frontiers in Immunology, 2025)
Relapsed/refractory acute myeloid leukemia (R/R AML) carries an extremely poor prognosis, particularly in patients who fail chimeric antigen receptor T-cell (CAR-T) therapy, with no effective treatment options currently available. We report a 35-year-old male with AML who experienced relapse after multiple lines of high-intensity chemotherapy. Salvage CAR-CLL1 therapy was administered, but the patient failed to achieve hematopoietic recovery or immune reconstitution, followed by rapid disease relapse within one month and progression to septic shock. At this critical juncture, conventional therapies proved insufficient. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) includes peripheral blood stem cell transplantation (PBSCT) and umbilical cord blood (UCB). The patient underwent combined UCB and PBSCT with donor lymphocyte infusion (DLI). He has since achieved sustained remission, though developed cutaneous and intestinal graft-versus-host disease (GVHD), which is currently under control. This case highlights that combined UCB and PBSCT with DLI may represent a potential therapeutic option for R/R AML following CAR-T therapy failure, warranting further investigation in similar high-risk scenarios.